Rapid estimation of echocardiographic peak velocity of circumferential fibre shortening (peak Vcf). Issue 1 (July 1981) - Ko, P; Boughner, D R; Paulsen, W J; Persaud, J A
Abstract : A transparent grid for estimating peak Vcf directly from the echocardiograph recording is described. Estimates so obtained were compared with peak Vcf measurements made by an echocardiographic digitising technique and with the angiographic ejection fraction in 13 patients with normal left ventricular function and 17 patients with impaired left ventricular function. No patient had angiographic segmental wall motion abnormalities. Significant linear correlations were found between peak Vcf derived by the simple manual technique and peak Vcf determined by the digitising technique and also between peak Vcf derived by the simple manual technique and the angiographic ejection fraction. Peak Vcf derived by the simple manual technique was found to be a reliable predictor of ventricular function, being more than 1.4 circumferences/s in 11 of 13 patients with angiographic ejection fractions greater than or equal to 55% and less than 1.4 in 14 of 17 patients with angiographic ejection fractions less than 55% (sensitivity 82%, specificity 85%). Thus, peak Vcf is an echocardiographic index that can be estimated rapidly and accurately without the need for digitising equipment and is well suited to general clinical use.